Relevansi Corporate Social Responsibility Terhadap Nilai-Nilai Ekonomi Islam Perspektif Mazhab Mainstream - Bustanul Arifin; Zainal Fanani; M Muflikhul Khitam (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2019)
Corporate social responsibility is a program dedicated to the interests of humanity and the environment and is intended to promote human beings, especially those around Environmental sustainability, especially where the company is operated. Corporate Social Responsibility is a concept relevant to the economic values of Islam in the point of view of the Mainstream sect. Researchers divide it into 3 principles, as follows: 1) Corporate Social Responsibility is faced with the principle of compound ownership (Multitype ownership) is relevant to the value of ownership (ownership) and the value of balance (equilibrium). Ownership values include private property and collective ownership. The balance value in terms of balance between right and obligation should be in care. Both of these values are derived from the value of Unity of God. 2) Corporate Social Responsibility if connected with the principle of freedom of action/endeavor (freedom to act) is to the company with the community that belongs to the concept of Khalifat That implies unity and brotherhood. Such freedom is in the context of economic freedom that corresponds to Sharia. 3) Corporate Social Responsibility Judging by the social Justice principles (social Justice) is demonstrated through its identity as part of the company's business ethics in which it applies the principle of fairness. Because in its implications, CSR emphasizes the concept of 3 P (profit, people, and planet) interrelated.